Development of an AC-DC buck power factor correction - Ibrahim, Muhammad Iskandar (2013)
Generally all devise used in industrial, commercial and residential applications need to undergo rectification for their proper functioning and operation. It connected to the non-linear loads which results in production of non-sinusoidal line current. Due to the increasing demand of these devices, the line current non-sinusoidal pose a major problem by degrading the power factor of the system thus affecting the performance of the devices. Hence there is a need to reduce the line current non-sinusoidal so as to improve the power factor of the system and led to designing of Power Factor Correction circuits. Power Factor Correction (PFC) involves two techniques, Active PFC and Passive PFC. In our project work we have designed an active power factor circuit using Buck Converter for improving the power factor. The advantage of using Buck Converter in power factor correction circuits is that better line regulation is obtained with appreciable power factor. Simulation and experimental are conducted to validate the theoretical analysis. The results show that the power factor can be improved.